Developing A Star-Up Business From A Management And Financial Perspective For Indonesian Workers In Korea - Haswan Yunaz; Enny Widayati; Zara Tania Rahmadi; Prisila Damayanty; Kim Soo Il (International Journal Of Community Service, 2023)
Many Indonesian citizens seek opportunities abroad, including becoming Indonesian workers in various countries, notably in South Korea. This phenomenon is further fueled by the global popularity of the Korean wave, attracting both Indonesian workers and students to Korea. With a significant proportion of Indonesia's population falling within the productive age range (15-64 years), there is a growing demand for diverse job opportunities. The recent boom in startup businesses, driven by technological advancements and government support, has provided a promising avenue for addressing these economic challenges. South Korea, known for its rapid technological development, offers an ideal environment for Indonesian workers in Korea to venture into startups. However, navigating the complexities of the Korean startup landscape, including fierce competition and intricate regulations, presents its own set of challenges. Building a robust network, understanding local regulations, and focusing on effective management and financial planning are essential for success. This community service initiative, conducted by IBI Kosgoro 1957 and the Indonesian Ambassador in Korea in collaboration with Kaya University and Busan University, aims to enhance the knowledge of Indonesian workers in Korea in the areas of startup business development, management, and finance. Through interactive seminars, discussions, and ongoing evaluations, this initiative seeks to empower Indonesian workers with the skills and insights needed to thrive in the competitive Korean market. The results and discussions from this initiative emphasize the importance of effective marketing strategies tailored to the Korean market, the significance of financial management in startup success, and the potential for Indonesian workers in Korea to build successful businesses by leveraging their unique experiences and networks. In conclusion, developing startup businesses in South Korea as Indonesian workers entails thorough market research, strong business planning, capable management teams, sound financial management, tailored marketing strategies, and adaptability. By effectively implementing these factors, Indonesian workers in Korea can enhance their prospects of establishing and growing successful startups in a competitive environment.